Secretome proteins regulate comparative osteogenic and adipogenic potential in bone marrow and dental stem cells - Kumar, A; Kumar, V; Rattan, V; Jha, V; Bhattacharyya, S (Elsevier, 2018)
Introduction Dental stem cells (DMSC) have been studied extensively since their early discovery. However, the data regarding osteogenic potential of DMSC with other cell types is sparse and the secretome proteins underlying these differences have not been explored. In this study, we have compared the osteogenic and adipogenic potential of DMSC with Bone Marrow Stem cells (BMSC) and reported the contribution of secretome proteins in controlling their differentiation. Methods Osteogenic potential of these stem cells was compared by mineralization assay, alkaline phosphatase (ALP) assay, immunofluorescence of dentine sialo phosphoprotein (DSPP) & qPCR for osteogenic genes. Adipogenic potential was compared by Oil Red O staining and qPCR for PPAR-γ, leptin & adipsin. Proteomic analysis of secretome was performed by employing WATERS nano Lc-MS/MS system. Results We observed a higher osteogenic potential in DMSC, especially dental pulp stem cells (DPSC) as compared to BMSC population but adipogenic potential was found to be better in BMSC as compared to DMSC. Deeper investigations into secretome of these cells by Lc-MS/MS revealed the presence of proteins pertaining to osteogenic and adipogenic lineage. Presence of some important proteins regulating osteogenic (DSPP, BMP7, DDR2, USP9X) and adipogenic differentiation (NCOA2, PEG10, LPA) in secretome of BMSC and DMSC reflected the role of paracrine factors during differentiation. Conclusion Our study provides first evidence regarding regulation of osteogenic/adipogenic potential by secretome proteins in DMSC and BMSC. DMSC especially DPSC and its secretome show an inherent tendency for higher osteogenic differentiation and lower adipogenic differentiation, these may be potential candidates for effective future therapy in osteoporosis where disturbance of osteocyte/adipocyte homeostasis is reported.